Analisis Hubungan Pemanfaatan Teknologi Informasi Sebagai Penunjang Prestasi Mahasiswa Fasilkom UNSRI melalui Metode Uji Chi-Square - Yunus, Hedi; Barata, Gusti; Ibrahim, Ali (P3M Politeknik Negeri Banjarmasin, 2019)
The chi-square test is a hypothesis test of the comparison between the frequency of observation and the frequency of expectations based on a particular hypothesis in each case or the data taken to be observed. From the research test with the title